2013
DOI: 10.1017/sjp.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Labelling Improves False Belief Understanding. A Training Study

Abstract: Abstract.A total of 104 children aged between 41 and 47 months were selected to study the relationship between language and false belief understanding. Participants were assigned to four different training conditions: discourse, labelling, control (all with deceptive objects), and sentential complements (involving non-deceptive objects). Post-test results showed an improvement in children's false belief understanding in the discourse and the labelling conditions, but not in the sentential complements with non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 37 publications
1
12
0
7
Order By: Relevance
“…The finding of this review also merits clinical consideration. Previous studies, involving TD children and children with ASD, found that ToM abilities can be improved with systematic training (e.g., Gevers, Clifford, Mager, & Boer, 2006;Lohmann & Tomasello, 2003;Sellabona et al, 2013). Similar interventions aiming to improve the ToM abilities of children with SLI may be contemplated as an adjunct to conventional language programs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding of this review also merits clinical consideration. Previous studies, involving TD children and children with ASD, found that ToM abilities can be improved with systematic training (e.g., Gevers, Clifford, Mager, & Boer, 2006;Lohmann & Tomasello, 2003;Sellabona et al, 2013). Similar interventions aiming to improve the ToM abilities of children with SLI may be contemplated as an adjunct to conventional language programs.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, longitudinal studies on preschool children consistently found that language abilities predicted later false-belief performance, whereas false-belief performance did not predict later language abilities (Astington & Jenkins, 1999;de Villiers & Pyers, 2002;Slade & Ruffman, 2005). Likewise, from experimental training studies it emerged that merely exposing children to systematic training on linguistic tasks was sufficient to cause improvement in their false-belief performance (Lohmann & Tomasello, 2003;Sellabona et al, 2013). Further evidence is provided by the consistent finding that deaf children of deaf parents have better ToM abilities than deaf children of hearing parents (Peterson & Siegal, 2000;Schick, de Villiers, de Villiers, & Hoffmeister, 2007), thus emphasizing the importance of linguistic environment and especially parent-child communication in facilitating children's ToM development (Schick et al, 2007).…”
Section: Language and Tommentioning
confidence: 99%
See 1 more Smart Citation
“…ToM is therefore a fundamental capacity that develops gradually from birth, and it is a crucial cognitive development that has been studied intensively in recent years. It may also be understood as a set of skills with different degrees of complexity that appear throughout development and expand our understanding of human behaviour (Serrat et al 2013 ). Several authors have studied the development of ToM in children, finding that, despite individual differences in relation to when these abilities are acquired, typically-developing children follow a similar developmental pattern, so the order of acquisition of these skills seems to be relatively stable (Wellman et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complements of communication verbs have been claimed to be indicative of a purer measure of complementation abilities precisely because they do not imply mental state concepts, removing this confounding variable with ToM. Studies of typically developing children showed that complementation with communication verbs is related to FB performance (de Villiers & de Villiers, 2012; de Villiers & Pyers, 2002; Durrleman & Franck, 2015; Hale & Tager‐Flusberg, 2003; Low, 2010; Ng, Cheung, & Xiao, 2010), and that complementation training improves false belief understanding (Durrleman et al, 2019; Lohmann & Tomasello, 2003; Sellabona et al, 2013). A limitation of previous studies is that CS understanding has been assessed by means of complements that were explicitly false.…”
Section: Introductionmentioning
confidence: 99%